Serum adiponectin levels in patients with acute coronary syndromes: Serial changes and relation to infarct size. (November 2015) - Alkofide, Hadeel; Huggins, Gordon S; Ruthazer, Robin; Beshansky, Joni R; Selker, Harry P
Background: The role of adiponectin in patients with acute coronary syndromes is incompletely defined. This study investigated adiponectin levels in patients with acute coronary syndromes and the association between adiponectin and 30-day infarct size and 1-year clinical outcomes. Methods: Retrospective analysis of 120 participants with acute coronary syndromes enrolled in the Immediate Myocardial Metabolic Enhancement During Initial Assessment and Treatment in Emergency care Trial. Blood levels were tested three times within 24 h of onset of ischaemic symptoms. Infarct size was measured at 30 days. The 1-year clinical outcome was the composite of all-cause mortality or hospitalization for heart failure. Results: Using linear mixed models, log adiponectin levels decreased by −0.005 µg/mL per hour ( p = 0.035). After stratifying the analysis by gender, there was no decrease in log adiponectin in men; however, levels decreased by −0.01 µg/mL per hour in women ( p = 0.02). Results of multivariable regression models showed no association between log adiponectin and infarct size ( β = −1.1, p = 0.64). Log adiponectin levels did not predict 1-year outcomes using Cox-proportional hazard models. Conclusion: There was a small decrease in plasma adiponectin shortly after symptoms of ischaemia, more noticeable in women. No relationship was found between adiponectin and infarct size or clinical outcomes. This adds to evidence showing no clear association between adiponectin and adverse outcomes in patients with acute coronary syndromes.